PENGETAHUAN WANITA USIA SUBUR 15-49 TAHUN TERHADAP PEMERIKSAAN PAP SMEAR DI KAMPUNG JAMBUDIPA RUKUN WARGA 07 KECAMATANSUKARAJA KABUPATEN BOGOR PROVINSI JAWA BARAT - Suroso; Riswahyuni Widhawati; Anah Nursanah (STIKes IMC Bintaro, 2020)
Cervical cancer whose health term is cervical cancer (cervical cancer) is a cancer that occurs in the uterine cervix, an area in the female reproductive organ which is the entrance to the uterus. One way to detect cervical cancer early is by using a Pap Smear test, Pap Smear or pap test is a specific test that is used and aimed at early detection of cervical cancer / cervical cancer. Not everyone must test this one. But people who live in homes are obligatory. Knowledge is a process of knowing, and this happens after people do sensing a particular object, Research that has been done shows that the characteristics of women of childbearing age can affect one's knowledge. The study aimed to determine the relationship of characteristics of women of childbearing age 15-49 years with knowledge of Pap Smear examination in the village of Jambudipaa RW. This study uses a quantitative method with a cross sectional research design. The population taken in this study were women of childbearing age 15-49 years in Kampung Jambudipa RW 07 with a total sample of 120 people, determination of the sample with purposive samling and calculated by the Slovin formula obtained results of 61 people. Data obtained through questionnaires that have been prepared. In this study using ChiSquare statistical analysis and obtained P value = 0.00 <alpha = 0.05 on the characteristics of women of childbearing age based on education which means that H0 is rejected, P value = 0.00 <alpha = 0.05 on characteristics of women of childbearing age based on work which means that H0 is rejected and obtained a value of P =0.04 <alpha = 0.05 on the characteristics of women of childbearing age based on information which means that H0 is rejected. -49 years with knowledge of Pap Smear examination in the village Jambudipa RW 07.